Case studies of weight cycling and menstruation in female japanese wrestlers - Matsunaga, S.; Shimizu, S.; Aizawa, K.; Satoh, M.; Wada, T.; Yumoto, K.; Kukidome, T. (International Journal of Wrestling Science, 2013)
Wrestling is a sport that requires highly frequent and high-intensity training in order to achieve victory. In addition, because wrestling is divided by weight class, many wrestlers practice weight control (reduction) in order to compete in an advantageous weight class. Female athletes face the problem of exercise-induced amenorrhea, in which highly frequent and high-intensity training results in abnormalities in menstruation and reproductive and physiological function. However, the relationship between rapid weight reduction throughout the competition season and menstruation in female wrestlers has not yet been demonstrated. Therefore, the present study continuously monitored body weight changes in female Japanese wrestlers throughout the competition season in order to grasp the actual state of their weight reduction and demonstrate its relationship with menstruation. METHODS: The subjects of the present study were five female wrestlers with high game level who have achieved high rankings in major domestic and international tournaments. The study covered the 2011 season, which is a period of 265 days. We conducted a factual survey on weight reduction and surveys related to body weight, body composition, and menstruation. RESULTS: Analyses of surveys related to body composition and menstruation showed that, during the season, the subjects went through four to five weight cycles, in which their body weight increased and decreased rapidly before and after matches. The subjects menstruated an average of 11 times per year, with one subject reporting an abnormal menstrual cycle. In addition, the subjects with normal menstruation showed a 5.8% relative reduction in body weight, whereas the subject with abnormal menstruation showed a relative reduction of 11.1%. CONCLUSIONS: Female Japanese wrestlers were observed to practice weight cycling throughout the competition season. Furthermore, a case study of the subject with an abnormal menstruation cycle suggested that repeated excessive weight reduction may affect the menstrual cycle.